Pengembangan Sistem Monitoring Prestasi Mahasiswa Berbasis Data Management Framework - Mia Karisma Haq; Rani Megasari; Eddy Prasetyo Nugroho (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2025)
The issue of limited structured data has often hindered the role of academic advisors in effectively monitoring students’ participation and achievements. At Universitas Pendidikan Indonesia (UPI), student achievement data, both academic and non-academic, is still largely processed manually through forms or online messaging groups, which does not support comprehensive analysis. This study aims to develop a Student Achievement Monitoring System based on the Data Management Framework (DAMA-DMBOK) to ensure that data management is standardized, integrated, and supports data-driven decision-making. The research method includes data collection through literature studies, observation, and interviews; designing the data architecture; formulating key performance indicators (KPIs); developing data visualization and reporting features; and evaluating data management maturity using the Data Management Maturity Assessment (DMMA). The implementation results show that the system has successfully increased the maturity level of data management in key areas such as Data Modeling and Design, Data Storage and Operations, Data Integration & Interoperability, Metadata Management, and Business Intelligence, reaching the Optimizing level. With its analytical dashboard, reporting features, and dynamic data filters, the system supports academic advisors in monitoring student achievement more accurately, continuously, and in a well-documented manner. This study is expected to serve as a reference for developing more adaptive and integrated student achievement monitoring systems at the study program level in higher education institutions.